Assessing the value of an E-mail knowledge extraction system - Sara Tedmori; Thomas Jackson (2009)
This paper reviews an approach to locating knowledge holders within organizations through the use of a well-established communication medium, E-mail. The approach has been used to develop the E-mail knowledge extraction (EKE) tool. EKE was then evaluated at an academic institution in the United Kingdom. This study represents the first effort to validate the viability of the E-mail medium as a source of knowledge profiling data, to be used for finding employees who possess the required knowledge. It also looks at the socio–ethical challenges associated with EKE’s adoption. The overall evaluation of EKE found it to be useful, interesting, easy and intuitive to use and of potential benefit to employees within organizations.